Successful management of a pregnant woman with Kasabach–Merritt syndrome and preeclampsia: A case report. Issue 28 (10th July 2020) - Yang, Yi; Guo, Zhiheng; Wang, Zhenpeng; Luo, Lili; Chen, Ying
Abstract: Introduction: Kasabach-Merritt Syndrome (KMS) is an extremely rare disease in adults, which lead to consumptive coagulopathy characterized by severe hypofibrinogenemia and thrombocytopenia. Patient concerns: a 25-year-old Chinese pregnant women complicated by preeclampsia and KMS presented with refractory postpartum hemorrhage and incision bleeding after cesarean section. Diagnosis: The diagnosis of KMS was made based on clinical manifestation of Kaposiform Hemangioendothelioma, severe hypofibrinogenemia and thrombocytopenia. Interventions: After a poor response to massive blood products transfusion for 1 week, corticosteroid treatment was initiated for 3 days. Outcomes: The patient reached a normal platelet count and a mild anemia within 4 weeks. Two months later, all laboratory values had returned to normal, and the incision was healing well. Conclusion: Pregnancy complicated by preeclampsia and surgery may have contributions for the development of Kasabach–Merritt syndrome. Corticosteroid is indicated in the episode of acute Kasabach–Merritt syndrome after the failure of massive blood transfusion.